Obesity and Cardiometabolic Risk Factors in Children and Young Adults With Non-classical 21-Hydroxylase Deficiency - de Vries, Liat; Lebenthal, Yael; Phillip, Moshe; Shalitin, Shlomit; Tenenbaum, Ariel; Bello, Rachel (Frontiers in Endocrinology, 2019)
Introduction: Classical congenital adrenal hyperplasia is associated with an increased risk of obesity and cardiometabolic disease. The aim of the study was to determine if this is also true for nonclassical congenital adrenal hyperplasia (NCCAH). Methods: A retrospective, cross-sectional, single-center study design was used. Data were collected on 114 patients (92 female) with NCCAH diagnosed during childhood/adolescence at a tertiary medical center. Patients were classified by treatment status at the last clinic visit. Outcome measures were assessed at diagnosis and the last clinic visit: weight status, body composition, blood pressure, lipid profile and glucose metabolism. The prevalence of overweight/obesity was compared to the parental prevalence, and for patients aged 11-20 years, to the Israeli National Survey. Results: Mean age was 7.9±4.2 years at diagnosis and 17.1±6.9 years at the last follow-up. At the last clinic visit, 76 patients were under treatment with glucocorticoids, 27 were off-treatment (previously treated), and 11 had never been treated. The rate of obesity (11.4%) was similar to the parental rates, and the rate of overweight was significantly lower. In patients 11-20 years old, rates of obesity or obesity+overweight were similar to the general Israeli population (11.4% vs. 15.1%, P=0.24 and 34.2% vs. 41.6% P=0.18, respectively). No significant difference was found between glucocorticoid-treated and off-treatment patients in any of the metabolic or anthropometric parameters evaluated, except for a lower mean fat mass (% of body weight) in off-treatment patients (23.0±7.7% vs. 27.8±6.8%, P=0.06). Systolic hypertension was found in 12.2% of NCCAH patients either treated or untreated. Conclusion: NCCAH diagnosed in childhood, whether treated or untreated, does not pose an increased risk of overweight, obesity, or metabolic derangements in adolescence and early adulthood.